Arcenautas. Guía de asesoramiento. Proyecto lingüístico de centro (2013) [CD-ROM]. ISBN 978-84-695-7507-9 - Jesús María García (Universidad de La Rioja, 2014)
Arcenautas. Guía de asesoramiento. Proyecto lingüístico de centro (2013) [CD-ROM]. ISBN978-84-695-7507-9.